Perbandingan Konsentrasi Detergen Akibat Pandemi COVID-19 dan Kebiasaan Baru (New Normal) Pada Kualitas Air Permukaan Kota Palangka Raya - Nani Apriyani; Achmad Imam Santoso; Dhymas Sulistyono (Universitas Riau, 2023)
Currently, the Indonesian nation is facing challenges that require human resources adapt to the COVID-19 pandemic situation. Has the discovery of a vaccine and the implementation of ongoing vaccination does not guarantee avoid the spread of COVID-19. Thus, the obligation to implement the protocol health continues. One of the health protocol policies is provide adequate hand washing facilities for the management public facilities. The behavior of washing hands with soap is part of the program Clean and Healthy Life Behavior (PHBS) in the household. Washing hands Using soap is an effective step to break the chain of transmission COVID-19. However, please note that hand soap contains detergent. The results of using detergent (hand soap) will produce residue in the form of liquid waste, which is then discharged into the environment directly cause the balance of nature to be disturbed, namely soil pollution which causes capable of changing soil pH, changing mineral content and nutrient disturbances from soil for plant life and polluted groundwater sources. On research In this case, identifying and analyzing the waste from washing hands with soap in public facilities can affect the environment and the amount of content detergents that dissolve in water and whether nature can neutralize water pollution that occurred before and after the COVID-19 pandemic.